2021
DOI: 10.1038/s41467-021-24467-0
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lung diseases are associated with gene expression programs favoring SARS-CoV-2 entry and severity

Abstract: Patients with chronic lung disease (CLD) have an increased risk for severe coronavirus disease-19 (COVID-19) and poor outcomes. Here, we analyze the transcriptomes of 611,398 single cells isolated from healthy and CLD lungs to identify molecular characteristics of lung cells that may account for worse COVID-19 outcomes in patients with chronic lung diseases. We observe a similar cellular distribution and relative expression of SARS-CoV-2 entry factors in control and CLD lungs. CLD AT2 cells express higher leve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 94 publications
0
34
0
Order By: Relevance
“…For instance, Gorelick et al 52 found the heart’s estrogen receptors are more sensitive than the liver upon the same exogenous chemical stimulation. The complications of respiratory tract 27 and liver 25 were more pronounced in COVID-19 patients; it is thus necessary to investigate the vulnerability of these tissues to infection. Our data also showed that alterations of ACE2 transcription in pulmonary and liver epithelial cells were more sensitive to chemical exposure than other cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Gorelick et al 52 found the heart’s estrogen receptors are more sensitive than the liver upon the same exogenous chemical stimulation. The complications of respiratory tract 27 and liver 25 were more pronounced in COVID-19 patients; it is thus necessary to investigate the vulnerability of these tissues to infection. Our data also showed that alterations of ACE2 transcription in pulmonary and liver epithelial cells were more sensitive to chemical exposure than other cells.…”
Section: Discussionmentioning
confidence: 99%
“…Given that clinical symptoms in kidney, 24 liver, 25 intestines, 26 and respiratory tract 27 are more pronounced in COVID-19 patients, the cells from these tissues are more susceptible and permissive to external stimulus. Hence, human cell lines representing these tissues, including A549 (pulmonary epithelial cell line), Beas-2B (bronchial epithelial cell line), NCM460 (intestinal epithelial cell line), and HepG2 (hepatic cell line), were adopted in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, some risk factors leading to the development of severe SARS-COV-2 infection have been identified including age, smoking status, ethnicity, and male sex. In addition to these risk factors, some comorbidities contribute to increasing hospitalization and mortality in COVID-19 disease, like a chronic obstructive pulmonary disease (COPD), hypertension, diabetes, and obesity [137] . Also, the transcriptome analysis of cells derived by patients with chronic lung diseases revealed the higher levels of genes linked directly to the efficiency of viral replication and to an improved inflammatory microenvironment supporting the susceptibility of these subjects to severe COVID-19 infection [137] .…”
Section: What About the Lung Lesions In Post-covid-19 Patients?mentioning
confidence: 99%
“…In addition to these risk factors, some comorbidities contribute to increasing hospitalization and mortality in COVID-19 disease, like a chronic obstructive pulmonary disease (COPD), hypertension, diabetes, and obesity [137] . Also, the transcriptome analysis of cells derived by patients with chronic lung diseases revealed the higher levels of genes linked directly to the efficiency of viral replication and to an improved inflammatory microenvironment supporting the susceptibility of these subjects to severe COVID-19 infection [137] . Conversely, the home use of drugs able to control cholesterol such as statins and anti-diabetic drugs such as metformin have been evidenced to lower the risk of death of COVID-19 patients [138] , [139] .…”
Section: What About the Lung Lesions In Post-covid-19 Patients?mentioning
confidence: 99%
“… 129 Besides, in the population of COVID‐19 patients with chronic lung injuries, AT2 cells exhibit preexisting dysregulation of viral infection associated genes, including verified and putative entry receptors and priming proteases (ACE2 and putative BSG, NPR1, HSPA5, as entry receptors; and TMPRSS2, CTSL, or FURIN, as priming proteases), which will facilitate SARS‐CoV‐2 infection. 130 …”
Section: Application Of Transcriptomics In Covid‐19 Pandemicmentioning
confidence: 99%